Спроба розгадати одну лексикографічну загадку - Задорожний, В.Б. (Лексикографічний бюлетень, 2014)
The article is devoted apparently to partial lexicographic problem — the stressing of the verb of the Ukrainian language гнітити and correspondingly to diff erent prefixal derivatives from this root. The fact is that dictionaries of the modern Ukrainian standard language interpret this word as having mobile accent paradigm with stressing scheme гнітúти — гнічý, гнíтиш… гнíтять. Meanwhile in living speech this verb generally has the fi nal accent with stressing scheme гнітúти — гнічý, гнітúш… гнітять. According to corresponding language material, taken from poetic works of the prominent Ukrainian poets of XIX–XX centuries, the author states that this verb is actually finally stressed. To our opinion such a fact throws light on the stated problem that as verb exactly with mobile stress B. Hrinchenko — the compiler of «Словаря української мови» (Dictionary of the Ukrainian language) uses in its poetic works, in which he repeated the same accent characteristic for him. Th is is only the ground and reason for chaotization of the stress in root гнітити as well as in its prefixal derivatives, when these characteristics are combined in some modern lexicographic sources. It seems as though partial problem reveals negative features of the modern Ukrainian lexicography in general.